A persuasão na propaganda dirigida a crianças: uma análise sob a perspectiva da gramática sistêmico-funcional - Martins, Simone Ruiz (2012)
The marketing techniques aimed at children have lead to them desire for the act of buying, creating needs sometimes superfluous. For the modern advertising, it is clear that mass consumption is only possible if the producer expresses a persuasive message under a guise of information (FUERTES-OLIVERA et al., 2001). Advertisers attract potential buyers through the use of different devices that have the text addressed as coauthors of advertising (Myers, 1994), matching the ads to talk, and showing persuasive trends (Rush, 1998). Authors such as Tanaka (1994) and Campos Pardillos (1995) emphasized the importance of these strategies in advertising, because this genre is a suitable example of covert communication. In this sense, they emphasized that successful advertising avoids pushing consumers to buy, but persuades them to that direction. The survey results indicate that the language in this context is not only verbal, but rather the images of characters from children's interests occupy most of the advertising, taking to the establishment of the persuasive power of this way of communication. Although we deal with multimodal texts daily, the phenomenon of the multi modal or composite text is a challenge for discourse analysts, particularly those working with linguistic tools fashioned to account for verbal texts. (MACKEN-HORARIK, 2004). This research, supported by the Systemic Functional Grammar and Linguistic Critical, aims to examine the food advertising addressed to children, focusing attention to create needs sometimes superfluous by analyzing the lexical-grammatical choices that are worth to persuade this segment of the population. With this purpose in mind, it should answer the following research questions: (a) what are the needs created in advertisements aimed at children? (B) these ads become effective by doing what?